GW24-e1729 The impact of hypertension history and baseline blood pressure levels on the cardiovascular outcomes in patients with atrial fibrillation. (1st October 2013) - Juan, Wang; Xing-hui, Shao; Han, Zhang; Bi, Huang; Li, Tian; Jun, Zhu; Yan, Liang; Hui-qiong, Tan; Yan-min, Yang
Abstract : Objectives: To explore the hypertension history and baseline blood pressure levelson the treatment of atrial fibrillation patients and the impact on one year follow-up cardiovascular outcomes. Methods: This prospective study consecutively enrolled patients presenting to an emergency department with atrial fibrillation at 20 hospitals in China from 2009 to 2011. Baseline data and treatment were recorded, all patients were followed up for one year, and major cardiovascular outcomes were recorded. A total of 2015 atrial fibrillation patients were enrolled, and all the patients were divided into 4 groups according to the previous history of hypertension and baseline blood pressure levels: group 1—patients have previous hypertension history and baseline blood pressure greater than 140/90 mmHg; group 2—patients have previous hypertension history and normal baseline blood pressure; group 3—patients have no hypertension history but baseline blood pressure greater than 140/90 mmHg; group 4—patients have no hypertension history and normal baseline blood pressure. Results: The average age of all patients was 68.5 ± 13.3 years, average systolic blood pressure and diastolic blood pressure were 131.9 ± 23.3, 79.9 ± 14.7 respectively. 1118 patients (55.5%) had a history of hypertension, and about 91.1% hypertension patient received antihypertensive treatment. The difference of mortality, no central nervous system embolism incidence and major bleeding incidence in the 4 groups was not statistically significant (p values were 0.685, 0.893, 0.204 respectively). The stroke incidences of group 1, 2, 3, 4 were 8.3%, 9.4%, 6.2% and 5.2% ( χ 2 = 8.721, p = 0.033). UnivariateCox regression analysis of risk factors for stroke, group 1 and 2 were the risk factors for stroke ( HR 1.613, 95%CI 1.054-2.469, p = 0.028; HR 1.83, 95%CI 1.179-2.864, p = 0.007) compared to group 4. The variables included in the multivariate Cox regression model was based on the baseline data and univariate analysis of meaningful factors as well as some common clinical risk factors, including hypertension groups, age, sex, history of coronary artery disease, history of heart failure, myocardial infarction history, history of rheumatic heart disease, a history of left ventricular hypertrophy, COPD history, history of stroke, history of diabetes, history of dementia, major bleeding history, diuretics, digoxin, beta-blockers, ACE inhibitors, ARB, clopidogrel, aspirin, warfarin, anti-arrhythmic drugs, statins. After adjusting the other risk factors, showed that hypertension and baseline blood pressure levels did not have independent predictive value (p = 0.737). And multivariate Cox regression analysis showed that age, sex, history of stroke, dementia/cognitive defects history were independent risk factor for one year follow-up of stroke in atrial fibrillation patients. Conclusions: History of hypertension and baseline blood pressure levels was not the risk factors for one year cardiovascular outcomes of atrial fibrillation patients. Elderly female atrial fibrillation patients with previous stroke and dementia history had a higher risk of stroke incidence.